ПРОБЛЕМИ РЕАЛІЗАЦІЇ ФУНКЦІЇ ОХОРОНИ ГРОМАДСЬКОГО ПОРЯДКУ ОРГАНАМИ МІСЦЕВОГО САМОВРЯДУВАННЯ - Беньковський, Сергій Юрійович (SUPREMANCE OF LAW, 2019)
The article analyzes the state of implementation of the function of public order protection by local selfgovernment bodies, where local public order bodies act not alongside local police bodies, but near them, solving a narrow range of tasks with a clear division of competence, proper control and in close interaction with them. It is concluded that such local law enforcement agencies should perform only some of the functions of the current preventive police, such as preventing and ending crime on the streets and in the home, administrative offenses, ensuring within the given powers of enforcement of decisions of local governments, etc.
Keywords: legal bases of realization of function of protection of public order by bodies of local self-government; activity of bodies of local self-government; social principles of creation of communal security enterprises